The Danish database for acute and emergency hospital contacts - Lassen AT; Jørgensen H; Jørsboe HB; Odby A; Brabrand M; Steinmetz J; Mackenhauer J; Kirkegaard H; Christiansen CF (Clinical Epidemiology, 2016)
Annmarie T Lassen,1 Henrik Jørgensen,2 Hanne Blæhr Jørsboe,3,4 Annette Odby,5 Mikkel Brabrand,6 Jacob Steinmetz,7 Julie Mackenhauer,8 Hans Kirkegaard,8 Christian Fynbo Christiansen9 1Department of Emergency Medicine, Odense University Hospital, Odense, 2Department of Surgery, Hospital of Northern Sjaelland, Hilleroed, 3Department of Emergency Medicine, Nykobing F Hospital, 4Department of Hospital Administration, Nykobing F Hospital, Nykøbing Falster, 5The Danish Clinical Registers, Registry Support Centre for Health Quality and Informatics, Aarhus, 6Department of Emergency Medicine, Hospital of South West Jutland, Esbjerg, 7Department of Anaesthesia, Rigshospitalet, Copenhagen University Hospital, Copenhagen, 8Research Center for Emergency Medicine, Aarhus University, 9Department of Clinical Epidemiology, Aarhus University Hospital, Aarhus, Denmark Aim for database: Aim of the Danish database for acute and emergency hospital contacts (DDAEHC) is to monitor the quality of care for all unplanned hospital contacts in Denmark (acute and emergency contacts).Study population: The DDAEHC is a nationwide registry that completely covers all acute and emergency somatic hospital visits at individual level regardless of presentation site, presenting complaint, and department designation since January 1, 2013.Main variables: The DDAEHC includes ten quality indicators – of which two are outcome indicators and eight are process indicators. Variables used to compute these indicators include among others day and time of hospital contact, vital status, ST-elevation myocardial infarction diagnosis, date and time of relevant procedure (percutaneous coronary intervention, coronary angiography, X-ray of wrist, and gastrointestinal surgery) as well as time for triage and physician judgment. Data are currently gathered from The Danish National Patient Registry, two existing databases (Danish Stroke Register and Danish Database for Emergency Surgery), and will eventually include data from the local and regional clinical logistic systems.Descriptive data: The DDAEHC also includes age, sex, Charlson Comorbidity Index conditions, civil status, residency, and discharge diagnoses. The DDAEHC expects to include 1.7 million acute and emergency contacts per year.Conclusion: The DDAEHC is a new database established by the Danish Regions including all acute and emergency hospital contacts in Denmark. The database includes specific outcome and process health care quality indicators as well as demographic and other basic information with the purpose to be used for enhancement of quality of acute care. Keywords: emergency care, emergency department, mortality, rehospitalization, quality of care